2015
DOI: 10.3758/s13423-015-0984-3
|View full text |Cite
|
Sign up to set email alerts
|

How feedback improves children’s numerical estimation

Abstract: Developmental change in children's number-line estimation has been thought to reveal a categorical logarithmic-to-linear shift in mental representations of number. Some have claimed that the broad and rapid change in estimation patterns that occurs with corrective feedback provides strong evidence for this shift. However, quantitative models of proportion judgment may provide a better account of children's estimation patterns while also predicting broad and rapid change following feedback. Here we test the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 26 publications
(44 reference statements)
2
22
0
Order By: Relevance
“…When this model is applied to a typical 0-1000 number line task, This model was later generalized to account for cases in which the observer makes use of additional reference points (for example, estimating the proportion of a cylinder that is partially filled with liquid by judging the liquid's level relative to a halfway point, rather than relative to the entire height of the cylinder; Hollands & Dyre, 2000). This work showed that the use of such reference points 1) produces a pattern of estimates with multiple S-shaped or inverse S-shaped curves or "cycles" (hence the term "cyclical power model" of proportion estimation; see Figure with this model are observed in children's number-line estimates Barth et al, 2016;Rouder & Geary, 2014;Slusser et al, 2013), as they are in adults' estimates of proportions using various continua (Cohen & Blanc-Goldhammer, 2011;Hollands & Dyre, 2000).…”
Section: For Reviews)mentioning
confidence: 83%
See 3 more Smart Citations
“…When this model is applied to a typical 0-1000 number line task, This model was later generalized to account for cases in which the observer makes use of additional reference points (for example, estimating the proportion of a cylinder that is partially filled with liquid by judging the liquid's level relative to a halfway point, rather than relative to the entire height of the cylinder; Hollands & Dyre, 2000). This work showed that the use of such reference points 1) produces a pattern of estimates with multiple S-shaped or inverse S-shaped curves or "cycles" (hence the term "cyclical power model" of proportion estimation; see Figure with this model are observed in children's number-line estimates Barth et al, 2016;Rouder & Geary, 2014;Slusser et al, 2013), as they are in adults' estimates of proportions using various continua (Cohen & Blanc-Goldhammer, 2011;Hollands & Dyre, 2000).…”
Section: For Reviews)mentioning
confidence: 83%
“…Converging evidence from multiple research groups, however, has recently shown that a different theoretical explanation offers a better explanation of performance on cognitive tasks, including number-line estimation tasks, that are commonly used to assess learning and development in numerical thinking Barth, Slusser, Kanjlia, Garcia, Taggart, & Chase, 2016;Cohen & Blanc-Goldhammer, 2011;Cohen & Sarnecka, 2014;Rouder & Geary, 2014;Slusser et al, 2013;Sullivan, Juhasz, Slattery, & Barth, 2011;see also Chesney & Matthews, 2013;Hurst, Monahan, Heller, & Cordes, 2014). These and other findings have fostered an ongoing debate, calling into question the hypothesis that a shift from logarithmic to linear mental representations of number underlies developmental change in numerical estimation and, in turn, observed improvements in formal math (see Barth, Slusser, Cohen, & Paladino, 2011;Opfer, Siegler, & Young, 2011).…”
Section: For Reviews)mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence in favor of this benchmark use is based on several sources, such as participants’ error rates and estimation latencies (Ashcraft and Moore, 2012), the superior fittings of one- and two-cycle power functions compared to logarithmic and linear functions on individuals’ estimation patterns (Barth and Paladino, 2011; Cohen and Blanc-Goldhammer, 2011; Slusser et al, 2013; Rouder and Geary, 2014; Barth et al, 2015; Reinert et al, 2015, though see Opfer et al, 2016), verbal reports of participants’ solution behavior (Newman and Berger, 1984; Peeters et al, 2016, 2017, unpublished), and, finally, eye-movement data (Schneider et al, 2008; Heine et al, 2010; Sullivan et al, 2011). Based on the evidence coming from all these sources, the development in children’s benchmark use can be depicted as follows.…”
Section: Introductionmentioning
confidence: 99%